2017
DOI: 10.1177/2158244017710493
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cultural Identity, Personality, and Social Exposure Correlates to College Women’s Intercultural Competence

Abstract: College students' intercultural competence (ICC) has become a focus of many higher education institutions. Yet, more work can be done to explore what variables play a role in this complex and multifaceted process. The current study investigated the association between the outcomes (i.e., cognitive, intrapersonal, and interpersonal domains of ICC), cultural identity (i.e., majority group and international status), personality traits (i.e., extraversion, agreeableness, conscientiousness, neuroticism, and intelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…To be more precise, cognitive and congruent criteria are aimed at forming the information and media competence of students; conative, constructive, and comic are aimed at forming the communication competence; creative and constructive are aimed at forming the technical competence; conformal is aimed at forming the consumer competence of schoolchildren. The presented types of competencies, in their entirety, determine the level of digital competence, that is, "the readiness and ability of a person to apply info-communication technologies confidently, effectively, critically, and safely in different spheres of life (information environment, communications, consumption, and technosphere) [5]. In turn, digital competence, along with cultural practices, online risks, online space characteristics, the concept of a digital personality, and the quality of digital world relations, determines the main areas of change and development vectors of digital socialization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To be more precise, cognitive and congruent criteria are aimed at forming the information and media competence of students; conative, constructive, and comic are aimed at forming the communication competence; creative and constructive are aimed at forming the technical competence; conformal is aimed at forming the consumer competence of schoolchildren. The presented types of competencies, in their entirety, determine the level of digital competence, that is, "the readiness and ability of a person to apply info-communication technologies confidently, effectively, critically, and safely in different spheres of life (information environment, communications, consumption, and technosphere) [5]. In turn, digital competence, along with cultural practices, online risks, online space characteristics, the concept of a digital personality, and the quality of digital world relations, determines the main areas of change and development vectors of digital socialization.…”
Section: Resultsmentioning
confidence: 99%
“…Digital socialization is considered to be a feature of a new form of socialization of a modern person, which reflects both the process of social adaptation and integration of a person in the context of digitalization of the life of society and the process of gaining new social experience based on online contexts by a person, as well as the use of information and communication technologies that form the so-called "digital identity". The digital identity, in turn, is the result of the digitization of personal data, individual needs, activities, relationships, biography, and habits [5]. The process of integration of the digital and real persons is inevitable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different research also demonstrated that personality characteristics influence intercultural partnerships, in addition to the language difference between local and foreign students (Aydın, 2020). Personality as a predictor of the intercultural competence of college students was investigated by Peifer and Yangchen (2017). Extraversion and agreeability were perceived to be essential variables of social interaction in their research.…”
Section: The Importance Of Problems Experienced By Foreign Studentsmentioning
confidence: 99%
“…Personality helps to understand many phenomena experienced in both educational and applied circumstances. Important topics such as managing conflict (e.g., Tehrani & Yamini, 2020) and creating inclusive environments (e.g., Peifer & Yangchen, 2017) can all be linked to underlying personality dispositions. For example, if it is known that a person is highly compliant or passive, questions can be posed allowing them to have a voice.…”
Section: Introductionmentioning
confidence: 99%